Effect of Primiparous Dam Age on Birth Performance of Aceh Cattle Calves at BPTU-HPT Indrapuri, Aceh - Sri Rahayu; Djoko Subagyo; Masrianto Masrianto; Rahmat Rahmat (Journal of Agriculture, 2026)
Aceh cattle are an important indigenous genetic resource in Indonesia due to their adaptability to tropical environments, disease resistance, and efficient utilization of low-quality feed. Birth performance is closely associated with subsequent growth and productivity; however, information regarding the effect of maternal age at first calving on calf birth traits in Aceh cattle remains limited. This study aimed to evaluate the birth performance of calves born to primiparous dams and to determine the influence of maternal age at first parturition on calf morphometric characteristics. The study was conducted at BPTU-HPT Indrapuri, Aceh Besar, Indonesia. Thirty-six Aceh calves born from primiparous dams aged 30–35 months were grouped into three maternal age categories (30–31, 32–33, and 34–35 months). Birth weight, body length, shoulder height, and chest circumference were measured within 0–3 days after birth. Data were analyzed using the Shapiro–Wilk test, Levene’s test, one-way ANOVA, and Tukey’s HSD test when required. Mean birth weight, body length, shoulder height, and chest circumference were 18.36 ± 2.50 kg, 51.39 ± 3.43 cm, 59.33 ± 3.33 cm, and 61.03 ± 3.92 cm, respectively. Maternal age at first calving did not significantly affect any birth trait observed (p > 0.05). Nevertheless, calves born from dams aged 32–33 months tended to show numerically superior performance. Maternal age at first parturition between 30 and 35 months does not significantly influence the birth performance of Aceh calves, although calving at 32–33 months provides favorable biological outcomes.